Destination image: an overview and summary of selected research (1974?2008). Issue 1 (3rd December 2010) - Aziz, Azlizam; Zainol, Nurul Amirah
Destination image area have been studied in over than three decades and have contributed to the management and marketing purposes in many tourism field. Sixty destination image journals beginning from 1974 to 2008 were collected in order to summarise and provide a useful overview to destination image researchers specifically and tourism researchers generally.